2020
DOI: 10.1093/bjsopen/zraa030
|View full text |Cite
|
Sign up to set email alerts
|

Discriminating complicated from uncomplicated appendicitis by ultrasound imaging, computed tomography or magnetic resonance imaging: systematic review and meta-analysis of diagnostic accuracy

Abstract: Background Discriminating complicated from uncomplicated appendicitis is crucial. Patients with suspected complicated appendicitis are best treated by emergency surgery, whereas those with uncomplicated appendicitis may be treated with antibiotics alone. This study aimed to obtain summary estimates of the accuracy of ultrasound imaging, CT and MRI in discriminating complicated from uncomplicated appendicitis Methods A systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 45 publications
1
35
0
Order By: Relevance
“…The pooled sensitivity of the speed bump sign is similar to RIPASA score (94%, 95% CI = 92-95%) [22], indicating the value of the speed bump sign in clinical applications. In addition, unnecessary CT scans can be avoided because of the similar pooled sensitivity between speed bump sign and CT (95%, 95% CI = 93-96%) [29]; consequently, medical cost and radiation exposure can be reduced. Although a low CoE was evaluated by GRADE methodology in pooled sensitivity because of some RoB and heterogeneity, taking the history of the speed bump sign in cases of suspected AA is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The pooled sensitivity of the speed bump sign is similar to RIPASA score (94%, 95% CI = 92-95%) [22], indicating the value of the speed bump sign in clinical applications. In addition, unnecessary CT scans can be avoided because of the similar pooled sensitivity between speed bump sign and CT (95%, 95% CI = 93-96%) [29]; consequently, medical cost and radiation exposure can be reduced. Although a low CoE was evaluated by GRADE methodology in pooled sensitivity because of some RoB and heterogeneity, taking the history of the speed bump sign in cases of suspected AA is strongly recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Although the useful diagnostic modalities for acute appendicitis include ultrasonography, CT, and magnetic resonance imaging, CT is generally accepted as the most reliable tool for the diagnosis of appendicitis (20). A previous meta-analysis has reported that CT has relatively low sensitivity and high negative predictive value for complicated appendicitis (mean sensitivity : 78%, mean specificity : 91%, mean positive predictive value : 74%, mean negative predictive value : 93%) (21). In our study, the diagnostic accuracy of CT for complicated appendicitis was comparable to that reported in the abovementioned study, supporting the reliability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis from our group compared all available studies on imaging modalities differentiating between uncomplicated and complicated appendicitis ( 47 ). Eleven studies using CT were found.…”
Section: Discriminating Complicated From Uncomplicated Appendicitismentioning
confidence: 99%
“…Eleven studies using CT were found. Summary estimates were 78% for sensitivity and 91% for specificity, resulting in a PPV of 74% and an NPV of 93% for diagnosis of complicated appendicitis ( 47 ). Results were highly heterogeneous, with sensitivities ranging from 28% to 95% ( 47 ).…”
Section: Discriminating Complicated From Uncomplicated Appendicitismentioning
confidence: 99%
See 1 more Smart Citation